A new synthetic route to the electron‐deficient ligand tris(3, 4, 5‐tribromopyrazol‐1‐yl)phosphine oxide. Issue 11 (1st November 2016) - Nicolas, Emmanuel; Cheisson, Thibault; Jong, G. Bas de; Tazelaar, Cornelis G. J.; Slootweg, J. Chris
Abstract : A new procedure for the synthesis of the electron‐poor ligand tris(3, 4, 5‐tribromopyrazol‐1‐yl)phosphine oxide is described. The structure displays a network of halogen bonds in the solid state. Abstract : The anionic tris(pyrazolyl)borates, or scorpionates, have proven to be extremely useful ligands. Neutral tris(pyrazolyl)methane ligands, however, are difficult to prepare and require numerous purification steps for a number of substitution patterns. We have previously outlined two different routes for accessing neutral tris(pyrazolyl) ligands. We describe here an adaptation of the previously published procedures for the synthesis of the electron‐poor ligand tris(3, 4, 5‐tribromopyrazol‐1‐yl)phosphine oxide, C9 Br9 N6 OP. Similar electron‐deficient ligands have been proven to unlock unique chemistry for the anionic scorpionates. The title perbrominated tris(pyrazolyl)phosphine oxide displays a network of halogen bonds in the solid state. All the bonds in the pyrazole ring are rather similar to the reported borate analogues, which makes this molecule promising as a ligand for applications where very electron‐poor metal complexes are required.